CRITICAL POINTS IN CARGO RAILROAD TRANSPORT (Perner's Contacts, 2009)
This paper describes the critical points in technological process of cargo railroad transport. Main concerns are three sections: registering of consignment, transport of consignment, and delivery of consignment to consignee. The critical points are demonstrated in the flowcharts of technological process with comment in text.
Keywords: cargo railroad transport; critical point